Experimental verification of the effectiveness of a method for evaluating and modeling the technical and tactical actions skilled basketball players - Sushko Ruslana Aleksandrovna (Kharkov National Pedagogical University, 2011)
We consider the direction of modeling technical and tactical actions basketball. Developed by means of correcting the training process, which affect the efficiency indicators of competitive activity. A method for calculating the index of the technical and tactical skills. Shows the technology assessment of technical and tactical skill based game roles. Recommended to perform high-speed serial two-point shots from various distances and angles, situational exercises in the fight for the ball. Recommended exercises to develop speed and power capabilities and improve concentration.